Aktivitas Promosi Melalui Media Sosial terhadap Proses Keputusan Pembelian Konsumen pada PD. Astiga Jaket Kulit Garut - Wati Susilawati (Jurnal Wacana Ekonomi, 2017)
This study aims to identify the Influence of Promotion Through Social Media Against Consumer Purchase Decision Process in PD. Astiga Leather Garut Jacket The research  method used in this research is descriptive  research  method and survey technique analysis. The sampling technique  used in this research  is  using non  propability sampling  technique  with  the total  population  of 190  people, while  the number of respondents is 66 respondents ie PD customers. Astiga  Leather  Garut Jacket. Based on the  results  of  data  processing  obtained correlation which shows there is a strong relationship between Promotion Through Social Media  Against  Consumer Purchase  Decision Process in PD. Astiga Leather Garut Jacket. While  from the  results  of  hypothesis testing obtained  that  the variable  Promotion  Through  Social  Media has  a  positive and  significant  impact on consumer purchasing decision  Decision in PD. Astiga Leather Garut Jacket. Based on the calculation of  coefficient  of  determination obtained. This. implies that the change in the variable value of the Purchase Decision process. Explained by the  variable of  Promotion Through  social  media influenced by other variables not examined.